Features of The Clinical Course and Risk Factors of Rheumatism in Adolescents - Darkhanbaevna, Gulyamova Gulbahor (American Journal of Bioscience and Clinical Integrity, 2026)
This article presents the results of a retrospective analysis of 38 clinical cases of adolescent children registered with a rheumatologist. The incidence pattern by gender and age is analyzed, and key risk factors and typical complications are identified.